Development of a web-based digital platform through the green education model on green chemistry material - Sitompul, Hamela Sari; Situmorang, Idawati (Institute of Computer Science (IOCS), 2026)
The Green Education model emphasizes contextual learning with real-world environmental issues, encourages collaboration, and encourages students to think critically in solving environmental problems such as pollution, waste, and energy use. This study aims to determine the conceptual and procedural feasibility according to material and media experts, teacher assessments, and student responses to the interactive learning website developed using the Green Education model for green chemistry. This research is a developmental study using the Lee & Owens model. Data collection methods used questionnaires and interviews. Data analysis techniques used were qualitative data analysis based on comments and suggestions, and quantitative data analysis based on average response scores and percentages. The results of this study demonstrated feasibility based on a Likert scale, with a score of 4.5 (very feasible) from material experts, 4.57 (very feasible) from media experts, 4.5 (very feasible) from teachers, and 87.07% (very feasible) from student responses. Based on the development and research results, it can be concluded that the interactive learning website using the Green Education model for green chemistry is conceptually and procedurally feasible as a teaching medium for chemistry learning.